Development of Inventory and Goods Lending Systems Using QR Code at Universitas Muhammadiyah Kotabumi - Risanda Ardela; Ryan Aji Wijaya (Universitas Panca Marga, 2026)
Asset and inventory management in higher education institutions is a crucial aspect of supporting academic operational efficiency. At Universitas Muhammadiyah Kotabumi (UMKO), the current inventory recording system and lending procedures are still conducted conventionally, leading to risks of data inaccuracy, slow information retrieval, and the potential loss of physical lending forms. This study aims to design and develop an integrated inventory and goods lending information system utilizing Quick Response (QR) Code technology. The system development method employed is the Waterfall model. This method was selected based on the characteristics of inventory systems that require structured development stages and comprehensive documentation. QR Code technology is implemented to automate item identification and accelerate lending transactions through mobile device scanning. The result of this research is a web-based application capable of providing real-time asset data, facilitating item tracking, and generating accurate inventory reports. The implementation of this system is expected to minimize human error, increase asset management transparency, and support the modernization of digital infrastructure within Universitas Muhammadiyah Kotabumi for more professional services.